Design Researchers Leading Interdisciplinary Teams - Stan Ruecker (Diseña, 2018)
This special issue of Diseña seeks to articulate and describe interdisciplinary examples of design-led research, posing questions such as: in what ways are such projects addressing matters of concern, what are the defining traits of such projects, and what has design brought that other disciplines could not? What legitimates the designer as a leader? What authority, expertise, or qualifications must a designer possess to lead? What is the tradeoff between a specific ability to form knowledge and an ability to assemble discrete pieces into a unified whole? What are the design methods or strategies used in research? And, are these methods succinctly defined at the commencing of a project or developed as the research unfolds?